2018
DOI: 10.1111/echo.13847
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐esophageal bicaval versus short‐axis view of interatrial septum in two‐dimensional transesophageal echocardiography for diagnosis and measurement of atrial septal pouches

Abstract: The mid-esophageal bicaval view should be preferable over mid-esophageal short-axis view of interatrial septum for the diagnosis and measurement of the left SP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The SP can be visualized in vivo using two methods, twodimensional transesophageal echocardiography (2D-TEE) and contrast-enhanced electrocardiogram-gated multi-slice computed tomography (MSCT) of the heart, but nothing is known about the accuracy of these two methods in detecting SPs [5,9,11]. Recent studies have also shown that the TEE with the three-dimensional (3D) modality may be superior over 2D examination [12].…”
Section: Introductionmentioning
confidence: 99%
“…The SP can be visualized in vivo using two methods, twodimensional transesophageal echocardiography (2D-TEE) and contrast-enhanced electrocardiogram-gated multi-slice computed tomography (MSCT) of the heart, but nothing is known about the accuracy of these two methods in detecting SPs [5,9,11]. Recent studies have also shown that the TEE with the three-dimensional (3D) modality may be superior over 2D examination [12].…”
Section: Introductionmentioning
confidence: 99%
“…ASP is poorly visualized in TTE, mainly because of the posterior position of the pouch in comparison to the other structures of the heart. The TEE with agitated saline is the gold standard for the diagnosis of the LASP [ 8 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…TEE-based evaluation of the LASP has the largest variation in prevalence estimates, likely related to operator and institutional differences in protocols used for image acquisition. Holda et al evaluated the inter-atrial septum of 146 patients using TEE with different imaging planes and found good agreement between the bi-caval and short-axis views (kappa 0.68) [29]. They found that the bi-caval view was slightly more sensitive in detecting LASP than the short-axis view, though the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%